Persepsi Stakeholder terhadap Pelaksanaan Corporate Social Responsibility: Kasus pada Bank Syariah di DIY - MB Hendrie Anto; Dwi Retno Astuti (Sinergi: Kajian Bisnis dan Manajemen, 2008)
Corporate Social Responsibility (CSR) is now getting more attention not only from the stockholder but also stakeholder. CSR is considered as a natural consequence of the existence of company in their society in order to maintain their profit in the long term. So, the benefit of CSR would be back to the company itself. In the perspective of Islamic bank, CSR is embedded in the ground of Islamic teachings which look at business as an entity to create maslahah in the society. Profit is necessary, but not sufficient to justify Islamic business. This paper is aim to indentify the perception among stakeholders on CSR practiced by Islamic banks in Daerah Istimewa Yogyakarta. Kruskal Wallis Test, Mann Whitney U-Test, and content analysis are utilized to analyze the data from 116 respondents which is selected with purposive method. In general, the result shows that there is no difference perception among stakeholders on the benefit of CSR practiced by Islamic banks in terms of imej building and competitiveness enhancement. In addition, Islamic banks are supposed to be more socially responsible than the conventional one. Keywords: CSR, perception, stakeholder, maslahah